PENGARUH ADOPSI IFRS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kurniawati, Lintang; Rahmawati, Rahmawati (JURNAL AKUNTANSI DAN AUDITING, 2014)
The study aims to know the influence of IFRS adoption toward earnings management that isassessed by three measure of earnings smoothing. They are diversification of net income (Î”NI),center ratio of net income (Î”CF), and correlation between accrual and cash flows. This Studyalso uses the control variabel to get other different influences such as leverage, growth, andROE. The population in this study is manufactured-based company listed in the Indonesian StockExchangein periode of 2007 and 2013. Sample are obtained by purposive sampling and thereare 226 companies that fit the criteria. Because there are abnormal data in the early testing,researcher does the reduction of data that contains outliers, until get 190 sample that can beused. The analysis uses the classic assumption test, and liniear analysis regression. To analyze,researcher use the SPSS 21 for windows. The findings show that there is influence IFRSadoption toward earnings management. Furthermore, earning management is lower after IFRSadoption. Control variable size influence the behaviour of manager in earnings managementpractically. Variable leverage, growth, and ROE do not influence behaviour manager in earningmanagement practically.